What Is Dissemination and Implementation Science?: An Introduction and Opportunities to Advance Behavioral Medicine and Public Health Globally. - Shelton, Rachel C.; Lee, Matthew; Brotzman, Laura E.; Wolfenden, Luke; Nathan, Nicole; Wainberg, Milton L. (International Journal of Behavioral Medicine, 2020)
There has been a well-documented gap between research (e.g., evidence-based programs, interventions, practices, policies, guidelines) and practice (e.g., what is routinely delivered in real-world community and clinical settings). Dissemination and implementation (D&I) science has emerged to address this research-to-practice gap and accelerate the speed with which translation and real-world uptake and impact occur. In recent years, there has been tremendous development in the field and a growing global interest, but much of the introductory literature has been U.S.-centric. This piece provides an introduction to D&I science and summarizes key concepts and progress of the field for a global audience, provides two case studies that highlight examples of D&I research globally, and identifies opportunities and innovations for advancing the field of D&I research globally.